From Understanding to Creating: Bridging AI Literacy and AI Fluency in K-12 Education - Rogers, Thomas; Carbonaro, Mike (Journal of Teaching and Learning, 2025)
This paper explores the distinctions and connections between AI literacy and AI fluency, drawing parallels with the historical development of other literacies such as computer literacy and digital fluency. The paper argues that while AI literacy focuses on understanding and evaluating AI technologies, AI fluency represents a higher-order competency encompassing innovation, ethical management, and creation with AI. Examining existing definitions identifies "creation" as a recurring theme differentiating fluency from literacy, where fluency implies the ability to generate novel solutions and artifacts using technology. The paper proposes a conceptual framework for AI literacy and fluency in K-12 education, emphasizing the need to develop both concurrently rather than sequentially. By fostering AI literacy through comprehensive professional development, educators can equip themselves and their students to engage with AI ethically and effectively. Simultaneously, cultivating AI fluency empowers students to utilize AI as a tool for innovation and problem-solving, going beyond passive understanding to actively shape the future of AI in education. The paper concludes that investing in teacher training and developing clear definitions of AI literacy and fluency are crucial steps toward integrating AI into K-12 education responsibly and effectively, preparing students to navigate the complexities of an increasingly AI-driven world.